STRATEGI ADAPTASI DAN INOVASI MODEL BISNIS DI ERA DISRUPSI DIGITAL - Akbar, Kurnia Rizza; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid proliferation of financial technology (fintech) poses a significant disruptive challenge to the established business models of Indonesia's conventional banking industry. This research provides a concise analysis of the specific adaptation strategies and business model innovations these incumbent banks are implementing to navigate the competitive digital landscape. Employing a qualitative methodology through a multiple case study design, this study delves into the strategic responses of three prominent conventional banks. Data was primarily collected via in-depth interviews with senior executives and analysis of corporate strategic documents. The summary of results reveals a multi-pronged strategic pivot, characterized by the adoption of open-banking ecosystems, significant investment in data analytics for customer personalization, and a fundamental overhaul of organizational culture to foster greater agility. The significance of these findings lies in providing a clear framework for how legacy organizations can strategically transform in the face of digital disruption, highlighting that success is contingent on a synergistic alignment of technology, strategy, and culture